High Antioxidant Egg Production Through Substitution of Soybean Meal by Indigofera sp., Top Leaf Meal in Laying Hen Diets - Palupi, R.; Abdullah, L.; Astuti, D.A.; Sumiati (International Journal of Poultry Science, 2014)
The aim of this research was to produce functional eggs that high antioxidant through substitution of soybean meal with Indigofera sp., top leaf meal in the laying hen diets. One hundred and sixty laying hens of Isa Brown strain, 30 weeks of age were kept into individual cages. Completely randomized design was used in this experiment, with 4 treatments and 4 replications. The treatment diets contained four kind combination of soybean meal (SBM) and Indigoferasp., top leaf meal (ITLM): T0 = diet contained 20% SBM and 0% ITLM; T1 = diet contained 17% SBM and 5.2% ITLM; T2 = diet contained 14% SBM and 10.4 ITLM; T3 = diet contained 11% SBM and 15.6 ITLM. The parameters observed were feed consumptions, egg production, egg quality and antioxidant activity. The results showed that substitution of soybean meal with Indigofera sp., top leaf meal not significantly (p>0.01) affected to feed consumptions, but significantly (p < 0.05) increased eggs production (83.63 to 92.65%), high significantly (p < 0.01) increased yolk colour, beta-carotene as well as vitamin A and decreased cholesterol content of the yolk. It was concluded that Indigofera sp., leaf meal could be used until 15.6% or substitute 45% soybean meal protein in the laying hen diets.